International history and organized crime (Rivista di Studi e Ricerche sulla criminalità organizzata, 2015)
The complexity of the current international scene and the sheer numbers of actors involved oblige the international relations historian to look beyond the paradigm of the central role of the state and to explore transnational phenomena. Within this framework, organized crime is, to all intents and purposes, a consolidated player in the international system and therefore subject to the historian’s particular scrutiny. In this essay the author addresses the issues, setting out the double contribution offered by international history to the study of organized crime: on one hand history can assist us in achieving a better understanding of the scenarios within which organized crime operates today, identifying the little-known aspects of the post cold-war era which make fertile ground for the consolidation of criminal processes; on the other, it is history that must help us to reflect on all that which, even in the area of cross-border organized crime, is rooted – or finds its precedents – much further back than the last decades, that is to say, in the history of the twentieth century.